Bovine babesiosis and anaplasmosis outbreaks diagnosed at INTA Salta, Argentina: 2006-2016 (FAVE Sección Ciencias Veterinarias, 2017)
A retrospective study of babesiosis and anaplasmosis outbreaks (tick fever, TF) was made, which occurred from 2006 to 2016 in Northwest Argentina (NWA), to evaluate clinical and epidemiological aspects of these diseases. From 4,398 specimens, 238 (5.4%) were associated with suspicions of TF and 106 of these cases (44.3%) were confirmed as TF outbreaks by microscopic observation of causal agents. Forty seven (44.3%) were due to Anaplasma marginale, 40 (37.7%) to Babesia bovis and 14 (13.2%) to Babesia bigemina. In five (4.7%) outbreaks of babesiosis, Babesia species were not determined. Outbreaks were diagnosed at 62 different cattle ranches in four provinces (Salta, Jujuy, Santiago del Estero and Chaco). The outbreaks occurred mostly during summer and autumn with a peak of incidence in April and null incidence in September for both diseases. Adult cows were the most affected cattle category. At least one death was recorded in 58% (61/106) of the outbreaks and the average number of deaths was determined as four by outbreak. We conclude that TF maintain its negative historical impact on cattle production of NWA.
Keywords: hemoparasites; tick borne diseases; case description; epidemiology